2016
DOI: 10.1021/acs.nanolett.6b03638
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of MgxCa1–xO on GaN by Atomic Layer Deposition

Abstract: Abstract:We demonstrate for the first time that a single-crystalline epitaxial Si-based power devices could not meet these demands due to the small band gap (1.1 eV) and low breakdown field of Si. 2 GaN could replace Si for future power applications because of its higher band gap (3.4eV) and higher breakdown field. One powerful method to examine the epitaxial film quality is cross-sectional TEM imaging. GaN. The well-defined film spots in the diffraction pattern (Fig. S2) peaks are seen in all three samples (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…The focus placed on the 'source' of advanced crystallography techniques allows students to learn what crystallography can do for their research and to network with professionals who can potentially provide a valuable collaboration. Students are typically keen to take advantage of such resources once they become available and apply what they have learned to complete their research projects (Das et al, 2017;Feng et al, 2017;Hwang et al, 2015;Lou et al, 2016;Powers et al, 2013Powers et al, , 2016Powers, Anderson et al, 2014;Ramadhar et al, 2015aRamadhar et al, ,b, 2017. A list of example beam time proposals that students submitted for their own research projects at two major user research facilities can be found in Table S1 in the supporting information.…”
Section: Impactmentioning
confidence: 99%
“…The focus placed on the 'source' of advanced crystallography techniques allows students to learn what crystallography can do for their research and to network with professionals who can potentially provide a valuable collaboration. Students are typically keen to take advantage of such resources once they become available and apply what they have learned to complete their research projects (Das et al, 2017;Feng et al, 2017;Hwang et al, 2015;Lou et al, 2016;Powers et al, 2013Powers et al, , 2016Powers, Anderson et al, 2014;Ramadhar et al, 2015aRamadhar et al, ,b, 2017. A list of example beam time proposals that students submitted for their own research projects at two major user research facilities can be found in Table S1 in the supporting information.…”
Section: Impactmentioning
confidence: 99%
“…The increase in magnitude of lattice parameter and cell volume of Ce doped SnO 2 are shown in Table 1 . The lattice parameter ‘a’ and ‘c’ of the Ce doped SnO 2 unit cell is found to increase linearly with the Ce concentration following Vegards law 39 , 40 which is shown in figure (see Supporting Information, Fig. S1 ).…”
Section: Resultsmentioning
confidence: 84%
“…The growth and development of high-quality dielectrics is of exceptional importance for their incorporation into next-generation GaN high-electron-mobility transistors (HEMTs) because of their great potential in the radio frequency and power switching applications for both lateral and vertical devices. , The high-quality interface and the high tolerance to the electric stress are the main criteria and underlying challenges to both the material selection and growth. Various materials have been adopted on the (Al)­GaN surface as the passivation and gate dielectric layer to improve the device performance and reliability, such as SiO 2 , SiN x , , AlN, Al 2 O 3 , AlON, , HfO 2 , ZrO 2 , MgGaO, and AlSiO . Among them, SiN x dielectrics grown by low-pressure chemical vapor deposition (LPCVD) demonstrated excellent time-dependent dielectric breakdown (TDDB) properties in GaN MIS-HEMT .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The high-quality interface and the high tolerance to the electric stress are the main criteria and underlying challenges to both the material selection and growth. Various materials have been adopted on the (Al)GaN surface as the passivation and gate dielectric layer to improve the device performance and reliability, such as SiO 2 , 3 SiN x , 4,5 AlN, 6 Al 2 O 3 , 7 AlON, 8,9 HfO 2 , 10 ZrO 2 , 11 MgGaO, 12 and AlSiO. 1 Among them, SiN x dielectrics grown by low-pressure chemical vapor deposition (LPCVD) demonstrated excellent timedependent dielectric breakdown (TDDB) properties in GaN MIS-HEMT.…”
Section: ■ Introductionmentioning
confidence: 99%